1992
DOI: 10.1007/bf00182391
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide sequence of the genome of the filamentous bacteriophage I2-2: Module evolution of the filamentous phage genome

Abstract: The nucleotide sequence of the circular single-stranded genome of the filamentous Escherichia coli phage I2-2 has been determined and compared with those of the filamentous E. coli phages Ff(M13, fl, or fd) and IKe. The I2-2 DNA sequence comprises 6744 nucleotides; 139 nucleotides less than that of the N- and I2-plasmid-specific phage IKe, and 337 (336) nucleotides more than that of the F-plasmid-specific phage Ff. Nucleotide sequence comparisons have indicated that I2-2, IKe, and Ff have a similar genetic org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 38 publications
0
19
0
Order By: Relevance
“…4). Examination of even this small subset of phages reveals evidence for both homologous recombination (involving genes I and IV of the phage maturation cassette [106]) and nonorthologous gene replacement (both for the replication gene cassette, noted earlier [123], and for the structural protein cassette). Thus, these phages, as with the tailed phages, cannot appropriately be described by a hierarchical taxonomy.…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…4). Examination of even this small subset of phages reveals evidence for both homologous recombination (involving genes I and IV of the phage maturation cassette [106]) and nonorthologous gene replacement (both for the replication gene cassette, noted earlier [123], and for the structural protein cassette). Thus, these phages, as with the tailed phages, cannot appropriately be described by a hierarchical taxonomy.…”
mentioning
confidence: 80%
“…Yet there is ample evidence for gene exchange by both homologous recombination (99) and illegitimate means (63,123) among bacteriophages. Therefore, not only should gene exchange be considered in constructing a taxonomic framework, it effectively invalidates any taxonomy that a priori assumes that gene exchange is nonexistent.…”
mentioning
confidence: 99%
“…Members of the Inoviridae from both genera (Inovirus and Plectrovirus) seem to enjoy frequent nonorthologous replacements within the module responsible for genome replication (Fig. 4B) (158,247,258,280). In addition, homologous recombination and intergenome rearrangements have been reported to play a role in the evolution of inoviruses (158,200,241).…”
Section: Inoviridaementioning
confidence: 99%
“…The nucleotide sequences of several filamentous phages of E. coli and P. aeruginosa have been determined (Beck et al, 1978;van Wezenbeek et al, 1980;Hill & Petersen, t982;Luiten et al, 1985;Peeters et al, 1985;Hill et al, 1991;Stassen et al, 1992). Comparative studies have revealed that although no DNA or amino acid sequence homology has been found, the overall gene organization is similar among these phages (Luiten et al, 1985;Stassen et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Comparative studies have revealed that although no DNA or amino acid sequence homology has been found, the overall gene organization is similar among these phages (Luiten et al, 1985;Stassen et al, 1992). Analysis of nucleotide sequences is the first step towards an understanding of the structure, function, organization and regulation of a 0001-1811 © 1994 SGM gene/genome.…”
Section: Introductionmentioning
confidence: 99%